2011
DOI: 10.1093/jxb/err207
|View full text |Cite
|
Sign up to set email alerts
|

FaPYR1 is involved in strawberry fruit ripening

Abstract: Although the plant hormone abscisic acid (ABA) has been suggested to play a role in the ripening of non-climatic fruit, direct genetic/molecular evidence is lacking. In the present study, a strawberry gene homologous to the Arabidopsis ABA receptor gene PYR1, named FaPYR1, was isolated and characterized. The 627 bp cDNA includes an intact open reading frame that encodes a deduced protein of 208 amino acids, in which putative conserved domains were detected by homology analysis. Using tobacco rattle virus-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
157
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(168 citation statements)
references
References 43 publications
11
157
0
Order By: Relevance
“…In both climacteric and nonclimacteric fruits, water deficiency generated a rise in ABA content, which accelerated ripening and was accompanied by changes in both metabolites and gene expression (Castellarin et al, 2007;Gong et al, 2010). This dual regulation has also been observed for other genes whose expression is also up-regulated throughout the strawberry fruit-ripening process (Cumplido-Laso et al, 2012;Daminato et al, 2013;Molina-Hidalgo et al, 2013) and molecularly supported both the proposal of PerkinsVeazie (1995) and the findings described by Chai et al (2011), and Medina-Puche et al (2014. This hormonally regulated expression pattern was also similar to that observed for the FaMYB10 gene (MedinaPuche et al, 2014), and it strengthens the relationship between FaMYB10 and FaEOBII.…”
Section: Faeobii Expression Is Hormonally Regulated In a Similar Way supporting
confidence: 82%
See 2 more Smart Citations
“…In both climacteric and nonclimacteric fruits, water deficiency generated a rise in ABA content, which accelerated ripening and was accompanied by changes in both metabolites and gene expression (Castellarin et al, 2007;Gong et al, 2010). This dual regulation has also been observed for other genes whose expression is also up-regulated throughout the strawberry fruit-ripening process (Cumplido-Laso et al, 2012;Daminato et al, 2013;Molina-Hidalgo et al, 2013) and molecularly supported both the proposal of PerkinsVeazie (1995) and the findings described by Chai et al (2011), and Medina-Puche et al (2014. This hormonally regulated expression pattern was also similar to that observed for the FaMYB10 gene (MedinaPuche et al, 2014), and it strengthens the relationship between FaMYB10 and FaEOBII.…”
Section: Faeobii Expression Is Hormonally Regulated In a Similar Way supporting
confidence: 82%
“…One-way ANOVA was performed on log-transformed data, and letters indicate significant differences (P , 0.05, LSD post hoc test). Taken together, these results indicate that FaEOBII expression is clearly regulated by both ABA content and auxin content of the fruit receptacle, which provides a putative molecular explanation for both the proposal of Perkins-Veazie (1995) and the findings described by Chai et al (2011), and Medina-Puche et al (2014.…”
Section: The Expression Of Faeobii Is Hormonally Regulated Throughoutsupporting
confidence: 67%
See 1 more Smart Citation
“…Since the discovery of Arabidopsis PYR/PYL/RCAR receptors, several orthologous genes had been discovered in important crops as tomato, rice, strawberry and soybean (Sun et al, 2011, Chai et al, 2011, Kim et al, 2012, Bai et al, ! 28 2013.…”
Section: Pyr/pyl/rcar Aba Receptors In Solanum Lycopersicummentioning
confidence: 99%
“…Results obtained in mature sweet cherry, which are very prone to abscission, suggested, however, that the ABA increase observed at late stages of fruit ripening was more likely related to Introduction ethylene in the development and ripening of climacteric fruits, such as nectarine and tomato, is well known (Ziliotto et al, 2008;Zhang et al, 2009b) since several reports suggested that the ABA accumulation just before the peak of ethylene production triggers ethylene biosynthesis responsible for climacteric fruit ripening (Zhang et al, 2001;Zhang et al, 2009a;Bastías et al, 2011). The role of ABA in non-climacteric fruit is less clear in spite of several reports have correlated the increase in ABA levels during fruit ripening with the increase in sugars content and the decrease in organic acids or fruit colouration, which are classical traits occurring during fruit maturation (Giribaldi et al, 2010;Chai et al, 2011;Ren et al, 2011;Gambetta et al, 2011;Li et al, 2012b).…”
Section: Role Of Aba In Plant Growth and Developmentmentioning
confidence: 99%